Integration of multiple health information systems for quality improvement of radiologic care. Issue 3 (3rd July 2017) - Wang, Kun; Zwart, Christine; Wellnitz, Clinton; Wu, Teresa; Li, Jing
ABSTRACT: In radiology, several Health Information Systems (HISs) are commonly used: Electronic Health Records (EHR), Radiology Information System (RIS), and Picture Archive and Communication System (PACS). Each HIS records partial and complementary information about the radiologic care process. Depending on the institution, the HISs that touch radiology can be distinct, disparate, and with different formats and meta information. We note no reported research on integrating multiple HISs to allow for an end-to-end tracking of the care patients receive. Therefore, the current Quality of Care (QoC) research is limited as it can only utilize data for partial workflow analysis. A comprehensive assessment of the QoC in radiology requires HISs be integrated such that key metrics can be extracted. We developed a novel technology called Department Data Depot (DDD) that integrates multiple HISs in radiology. We propose nine metrics defined upon DDD data measuring various dimensions of care quality. To demonstrate the clinical utility of DDD, we developed and deployed the Radiology Quality Dashboard (RQD) at Mayo Clinic in Arizona. Four use cases illustrate how RQD is used to assist the clinical practice. A case study on how DDD enabled an effective intervention for reducing lengthy radiologist turnaround times (TATs) is presented.